The Impact of Health Care Restructuring on Nosocomially Acquired Blood Stream Infections - Geoffrey D Taylor; Margare McKenzie; Teresa Kirkland; Maureen Buchanan-Chell; Rhoda Wiens (Canadian Journal of Infectious Diseases)
OBJECTIVE: To assess the impact of the health care restructuring, which occurred in Alberta in 1995, on the occurrence of nosocomial blood stream infection and risk factors for these infections at the University of Alberta Hospital.